National and international surveillance of antibiotic resistance 2 - Livermore, David (Henry Stewart Talks, 2009)
Sets of surveillance data: routine data collection & sentinel surveillances, Two approaches to resistance surveillance using lab data, Information for action and to assess success
Updated at 2016/08/31